2016
DOI: 10.1155/2016/8219326
|View full text |Cite
|
Sign up to set email alerts
|

p-Channel and n-Channel Thin-Film-Transistor Operation on Sprayed ZnO Nanoparticle Layers

Abstract: Both n-channel and p-channel thin-film transistors have been realized on ZnO nanoparticle (NP) layers sprayed onto quartz substrates. In this study, nitrogen-doped ZnO-NPs were synthesized using an arc-discharge-mediated gas-evaporation method that was recently developed. Sprayed NP layers were characterized by scanning electron microscopy and Hall effect measurements. It was confirmed that p-type behaving NP layers can be obtained using ZnO-NPs synthesized with lower chamber pressure, whereas n-type conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Over the past decade, nanomaterials emerged as promising commodities in many fields including cosmetics, healthcare, biomedical, food and feed, drug-gene delivery, environment, health, mechanics, optics, chemical industries, electronics, space industries, energy science, catalysis, light emitters, single electron transistors, nonlinear optical devices, and photoelectrochemical applications [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, nanomaterials emerged as promising commodities in many fields including cosmetics, healthcare, biomedical, food and feed, drug-gene delivery, environment, health, mechanics, optics, chemical industries, electronics, space industries, energy science, catalysis, light emitters, single electron transistors, nonlinear optical devices, and photoelectrochemical applications [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To form particle layers [16], 30 mL of dispersion fluid were sprayed to heated quartz substrates using standard airbrush, as shown in Figure 1, with 5-s intervals for 15 min. The setting value of the hot plate temperature was 500°C (the actual surface temperature was about 370°C determined using thermographic measurement).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, by using the ZnO-NPs synthesized in our laboratory [14,15], not only n-channel but also p-channel back-gate TFTs on Si/SiO2 substrates were successfully demonstrated by using the simple and easy spraying method [16], providing high expectation to realize complementary logic circuits using ZnO-based NP-layers. However, the performances of obtained TFTs were insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have developed several protocols for the fabrication of ZnO NPs with both p-type and n-type conductivity [ 19 , 20 , 21 ]. Though it contained the influence of many boundaries, Itohara et al, reported the p-type conductivity (mobility 5~7 cm 2 /Vs and carrier concentration + 2.0 × 10 12 ~ + 2.7 × 10 12 cm −3 ) of nitrogen-doped ZnO NPs films [ 22 ]. We previously demonstrated the operation of semiconductor devices, such as thin-film transistors [ 22 ] and UV LED [ 23 ], using nitrogen-doped ZnO NPs for p-type layers.…”
Section: Introductionmentioning
confidence: 99%
“…Though it contained the influence of many boundaries, Itohara et al, reported the p-type conductivity (mobility 5~7 cm 2 /Vs and carrier concentration + 2.0 × 10 12 ~ + 2.7 × 10 12 cm −3 ) of nitrogen-doped ZnO NPs films [ 22 ]. We previously demonstrated the operation of semiconductor devices, such as thin-film transistors [ 22 ] and UV LED [ 23 ], using nitrogen-doped ZnO NPs for p-type layers. Fujita et al, demonstrated near-ultraviolet, homojunction LEDs based on nitrogen-doped ZnO NP layers on a GZO (Ga-doped ZnO) film by a simple coating process [ 23 ].…”
Section: Introductionmentioning
confidence: 99%